Pengaruh Beban Kerja dan Lingkungan Kerja Terhadap Kinerja Pegawai - Muhammad Nur Deni Musa Musa; Herman Surijadi (Univiversitas Dr. Djar Wattiheluw, 2020)
The purpose of this study was to examine and analyze the effect of workload and work environment on employee performance. The population of this study were all employees of the Civil Registry Office of Buru Regency. The sampling technique used a census technique with a final sample size of 39 respondents. The research data collection was obtained through a questionnaire instrument while the research data analysis used multiple linear regression analysis. The results showed that the workload and work environment proved to have a positive and significant effect on the performance of the employees of the Buru Regency Civil Registry. This can be proven through the regression coefficient of workload and work environment which, if it increases, will be followed by an increase in job satisfaction. Thus it can be said that an increase in the value of workload and work environment will improve the performance of employees of the Civil Registry Office of Buru Regency.